FASN contributes to ADM resistance of diffuse large B-cell lymphoma by inhibiting ferroptosis via nf-κB/STAT3/GPX4 axis - Xing Zhong; Weiwei Zhang; Weiming Zhang; Nasha Yu; Wuping Li; Xiangxiang Song (Cancer Biology & Therapy, 2024)
Drug resistance is a critical impediment to efficient therapy of diffuse large B-cell lymphoma (DLBCL) patients. Recent studies have highlighted the association between ferroptosis and drug resistance that has been reported. Fatty acid synthase (FASN) is always related to a poor prognosis. In this study, we investigate the impact of FASN on drug resistance in DLBCL and explore its potential modulation of ferroptosis mechanisms. The clinical correlation of FASN mRNA expression was first analyzed to confirm the role of FASN on drug resistance in DLBCL based on the TCGA database. Next, the impact of FASN on ferroptosis was investigated in vitro and in vivo. Furthermore, a combination of RNA-seq, western blot, luciferase reporter, and ChIP experiments was employed to elucidate the underlying mechanism. The prognosis for patients with DLBCL was worse when FASN was highly expressed, particularly in those undergoing chemotherapy for Adriamycin (ADM). FASN promoted tumor growth and resistance of DLBCL to ADM, both in vitro and in vivo. It is noteworthy that this effect was achieved by inhibiting ferroptosis, since Fer-1 (a ferroptosis inhibitor) treatment significantly recovered the effects of silencing FASN on inhibiting ferroptosis, while Erastin (a ferroptosis inducer) treatment attenuated the impact of overexpressing FASN. Mechanistically, FASN activated NF-κB/STAT3 signaling pathway through phosphorylating the upstream IKKα and IκBα, and the activated STAT3 promoted GPX4 expression by directly binding to GPX4 promoter. FASN inhibits ferroptosis in DLBCL via NF-κB/STAT3/GPX4 signaling pathway, indicating its critical role in mediating ADM resistance of DLBCL.